UKURAN DEWAN KOMISARIS DAN KOMITE AUDIT TERHADAP PROFITABILITAS PADA PERUSAHAAN PERTAMBANGAN - Aureillia, Vira; Rahmah, Mulia (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2025)
This study was conducted to determine the effect of the size of the board of commissioners and the audit committee on profitability in mining companies listed on the Indonesia Stock Exchange (IDX) in 2021-2023. This research was conducted to Indonesia Stock Exchange (IDX) Listed Mining Companies from the year 2021 to the year 2023. The sample determination method used a purposive sampling method with the sample used was 22 companies. Data analysis techniques used with descriptive statistics, classical assumption tests (data normality test, multicollinearity test, autocorrelation test, and heteroscedasticity test), and hypothesis testing with multiple linear regression (simultaneous hypothesis testing (f test), partial hypothesis testing (t test), and coefficient of determination test) which were processed using SPSS V.26. Based on the results of the study, simultaneously, the Size of the Board of Commissioners and the Audit Committee have no effect on profitability. The Size of the Board of Commissioners and the Audit Committee, individually, also do not affect profitability.